2013
DOI: 10.1080/17408989.2012.726976
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between coach leadership, the coach–athlete relationship, team success, and the positive developmental experiences of adolescent soccer players

Abstract: The relationship between coach leadership, the coach-athlete relationship, team success, and the positive developmental experiences of adolescent soccer players

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
177
3
31

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(227 citation statements)
references
References 40 publications
16
177
3
31
Order By: Relevance
“…Jones' (2009) work, in particular, recommends a pedagogical turn to coaching, one that involves coaches caring for their athletes beyond the teaching of sport-specific skills. Indeed, individual consideration, intellectual stimulation and appropriate role modelling have been found to stimulate positive youth development (Vella, Oades, and Crowe 2012). However, we contend that a commodity-driven orientation is a significant part of contemporary high-performance sport and that it must be acknowledged if one is to look at learning cultures and learning in high-performance sport.…”
Section: Purpose Of Trainingmentioning
confidence: 99%
“…Jones' (2009) work, in particular, recommends a pedagogical turn to coaching, one that involves coaches caring for their athletes beyond the teaching of sport-specific skills. Indeed, individual consideration, intellectual stimulation and appropriate role modelling have been found to stimulate positive youth development (Vella, Oades, and Crowe 2012). However, we contend that a commodity-driven orientation is a significant part of contemporary high-performance sport and that it must be acknowledged if one is to look at learning cultures and learning in high-performance sport.…”
Section: Purpose Of Trainingmentioning
confidence: 99%
“…Other research has found coach autonomy support to be associated with personal and social skills, cognitive skills, goal setting, and initiative (Cronin & Allen, 2015). Research conducted on adolescent soccer players found that team success had no correlation with the overall developmental experience; however, coach transformational leadership behavior and the coach-athlete relationship appeared to be the best predictors of athletes' positive developmental experiences such as goal setting, initiative, and personal and social skills (Vella, Oades, & Crowe, 2013).…”
Section: Positive/negative Youth Developmentmentioning
confidence: 99%
“…According to Weiss [8], sport provides a set of naturally occurring opportunities of which adult leaders may use to facilitate the acquisition of developmental assets. Vella et al [9] have also inferred that both "winning" and "losing" in youth sports provide an opportunity for developmental gains to be promoted by the coach.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional research demonstrates that the positive developmental experiences of young athletes are associated with coaches' transformational leadership behaviour [9]. In addition, a test of transformational leadership theory amongst adolescent athletes has shown that coach transformational leadership behaviour predicts athlete outcomes at both an individual and team level [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation